2018
DOI: 10.1111/eva.12737
|View full text |Cite
|
Sign up to set email alerts
|

New insights into host adaptation to swine respiratory disease revealed by genetic differentiation and RNA sequencing analyses

Abstract: Swine respiratory disease (SRD) causes massive economic losses in the swine industry and is difficult to control and eradicate on pig farms. Here, we employed population genetics and transcriptomics approaches to decipher the molecular mechanism of host adaptation to swine respiratory disease. We recorded two SRD‐related traits, the enzootic pneumonia‐like (EPL) score and lung lesion (LL) levels, and performed four body weight measurements, at ages of 150, 180, 240, and 300 days, in a Chinese Bamaxiang pig her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
(79 reference statements)
1
4
0
2
Order By: Relevance
“…The most frequent findings in pig lungs at the abattoir are cranioventral pulmonary consolidation, categorised as enzootic pneumonia-like lesions, particularly caused by M. hyopneumoniae. Despite all the efforts performed to reduce economic losses caused by these pathogens, M. hyopneumoniae continues to be an important concern to worldwide swine herds (Zhang et al 2018). The prevalence of M. hyopneumoniae, PRRSV and SIV infections was high in this research (Table 4), though similar to other reported European studies (Falk and Lium 1991;Lium and Falk 1991;Grest et al 1997;Cleveland-Nielsen et al 2002;Fraile et al 2010;Meyns et al 2011;Fablet et al 2012;Merialdi et al 2012).…”
Section: Resultssupporting
confidence: 84%
“…The most frequent findings in pig lungs at the abattoir are cranioventral pulmonary consolidation, categorised as enzootic pneumonia-like lesions, particularly caused by M. hyopneumoniae. Despite all the efforts performed to reduce economic losses caused by these pathogens, M. hyopneumoniae continues to be an important concern to worldwide swine herds (Zhang et al 2018). The prevalence of M. hyopneumoniae, PRRSV and SIV infections was high in this research (Table 4), though similar to other reported European studies (Falk and Lium 1991;Lium and Falk 1991;Grest et al 1997;Cleveland-Nielsen et al 2002;Fraile et al 2010;Meyns et al 2011;Fablet et al 2012;Merialdi et al 2012).…”
Section: Resultssupporting
confidence: 84%
“…found that SNRPA is highly expressed in swine respiratory diseases, which supports the hypothesis that it has a role in susceptibility to respiratory diseases. 38 However, some studies reported that anti-U1 snRNP was associated with reduced PAH risk. 39 , 40 Therefore, this controversial issue requires more research to be fully addressed.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate whether there is genetic differentiation exist in scrotal hernia pigs and health pigs, we divided the affected pigs and the unaffected pigs into two groups, as the method did by Zhang et al (2019) then assessed allele frequency differentiation using the unbiased genetic differentiation estimated of the fixation index (Fst). Akey et al have fully described estimation of unbiased Fst fixation index in his paper using SNP dataset (Akey et al, 2002).…”
Section: Genetic Differentiation Analysismentioning
confidence: 99%
“…The negative Fst didn’t have any biological interpretation and were set to 0 to fit the definition of Fst ranging from between 0 and 1 (Wright, 1951). The top 1% of loci according to genetic differentiation values was served as candidate regions to host resistance or susceptibility to pig scrotal hernia (Zhang et al, 2019).…”
Section: Genetic Differentiation Analysismentioning
confidence: 99%